Preparation method of zinc negative electrode with highly exposed (101) crystal face etched by citric acid and application of zinc negative electrode in aqueous zinc ion battery negative electrode

The zinc negative electrode material that forms a highly exposed (101) crystal surface and ZnS SEI protective layer through citric acid etching solves the stability and safety problems of traditional zinc negative electrodes during circulation, realizes rapid migration and uniform deposition of zinc ions, and improves the stability and kinetic performance of the battery.

CN119601575APending Publication Date: 2025-03-11QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411707729.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

During the circulation process of traditional commercial zinc anode, the rapid growth of dendrites, the flammable and explosive battery, and the reduction of discharge depth of the battery, affecting the stability and safety of the battery.

Method used

The surface of commercial zinc foil was etched at room temperature using citric acid, exposed a large number of (101) crystal surfaces, and the activated zinc negative electrode was formed by ammonium persulfate treatment, which promoted the rapid formation of the ZnS solid electrolyte membrane and formed a bifunctional zinc ion battery negative electrode material with highly exposed (101) crystal surfaces and ZnS SEI.

Benefits of technology

The rapid migration and uniform deposition of zinc ions are achieved, dendrites are inhibited and hydrogen evolution reactions are inhibited, the stability and kinetic performance of the battery are improved, the cycle life of the battery is extended, and the safety is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005154910620000011
    Figure HDA0005154910620000011
  • Figure HDA0005154910620000012
    Figure HDA0005154910620000012
  • Figure HDA0005154910620000013
    Figure HDA0005154910620000013
Patent Text Reader

Abstract

The invention relates to a preparation method of a negative electrode material for greatly exposing (101) crystal faces of a traditional commercial zinc foil by adopting a citric acid etching reaction and application of the negative electrode material in water-based zinc ion battery negative electrode protection. And the crystal faces (100) and (002) are etched off by using citric acid, and a large amount of the negative electrode material of the crystal face (101) is exposed. When applied to a negative electrode of a water-based zinc ion battery, the negative electrode material can improve the migration and nucleation capabilities of zinc ions in the negative electrode, can accelerate the dynamic process of rapid and uniform deposition of the zinc ions, and also can improve the stability of the battery. The stability and the dynamic performance of the negative electrode can be greatly improved, zinc ions can achieve rapid migration and uniform deposition on the surface of the negative electrode, and a good inhibition effect on hydrogen evolution and corrosion behaviors is achieved. Research finds that a layer of ZnS solid electrolyte membrane (SEI) protection layer is formed on the surface of the highly exposed Zn (100) negative electrode in the circulation process to prevent direct contact between an exposed crystal face and electrolyte, so that side reactions such as water decomposition and the like are inhibited, interface free energy is reduced, transfer kinetics of zinc ions is promoted, and the service life of the negative electrode is prolonged. And nucleation and deposition of uniform zinc ions are facilitated. The method for protecting the negative electrode of the aqueous zinc ion battery is simple and safe to operate, shows excellent reversibility, and can stabilize the output of the battery in a whole battery in practical application, and the method for protecting the negative electrode of the aqueous zinc ion battery is provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the field of preparation of negative electrodes for aqueous zinc ion batteries, and in particular refers to a zinc negative electrode with a high exposed (101) crystal face formed by etching with citric acid on the surface of a commercial zinc foil, thereby promoting rapid formation of a solid electrolyte membrane (SEI) of ZnS and applying it in the negative electrode of an aqueous zinc ion battery. [Background technology]

[0002] With the rapid development of society, traditional energy plays a decisive role in it. However, due to its non-renewable characteristics, new energy storage devices have become an important guarantee for the sustainable development of society. Among them, aqueous zinc-ion batteries are considered to be the most promising secondary batteries due to their high theoretical specific capacity (820mAh / g), low redox potential (-0.76V vs. SHE (standard hydrogen electrode)), safety and low cost.

[0003] However, the traditional commercial zinc anode has poor stability, which is a drawback that hinders its commercial application, mainly manifested in the following aspects:

[0004] (1) The traditional zinc negative electrode will experience random deposition of zinc ions during the cycle, which will inevitably lead to local excessive accumulation and cause the "tip effect". The increase in local electric field strength leads to the rapid growth of dendrites, which eventually pierces the diaphragm and causes an internal short circuit in the battery.

[0005] (2) The hydrogen evolution reaction during battery operation becomes a potential safety hazard that makes the battery flammable and explosive;

[0006] (3) The hydrogen evolution reaction causes the pH near the negative electrode to increase, and the hydroxide ions react with the electrolyte to form a non-conductive byproduct [ZnSO4·3Zn(OH)2·nH2O], which leads to a decrease in the battery discharge depth and a significant decrease in coulombic efficiency, which is not conducive to the long-term stable cycle of the battery.

[0007] Studies have shown that the zinc atoms on the (100) crystal plane are arranged vertically in a hexagonal shape, which is not conducive to the uniform deposition of zinc ions and ultimately leads to the formation of dendrites; the zinc atoms on the (002) crystal plane are deposited and stacked along the plane, but the deposition rate is slow, which is not conducive to long-term cycle stability. In comparison, the tight stacking pattern and fast reaction kinetics of the (101) crystal plane can not only avoid the problem of dendrites, but also solve the problem of long-term cycle stability, and has become a hot topic of current research.

[0008] Therefore, a stable and safe zinc negative electrode becomes an important way to open up the commercial development of aqueous zinc ion batteries, and the present invention is specially proposed. [Summary of the invention]

[0009] In view of the problems existing in traditional commercial zinc negative electrodes, one of the purposes of the present invention is to provide a new type of negative electrode, which adopts a method and strategy of etching with citric acid at room temperature to expose a large number of (101) crystal planes, which can realize the rapid movement and rapid deposition of zinc ions in the negative electrode and has excellent kinetic performance; at the same time, after a short cycle, the negative electrode will produce a layer of ZnS solid electrolyte film (SEI) on the surface. The protective layer is hydrophilic and can realize the rapid removal of water from the solvated structure of hydrated zinc ions, thereby accelerating the rate-determining step in the electrochemical step and further improving the kinetic performance of the battery.

[0010] The second object of the present invention is to provide a method for preparing a dual-functional zinc ion battery negative electrode material with a highly exposed (101) crystal face and a ZnS SEI formed by citric acid etching, and the specific steps are as follows:

[0011] 1. First, polish the surface of the commercial zinc foil to remove the dense passivated zinc oxide on the surface. Then, ultrasonically treat the polished zinc foil with ethanol, deionized water, and ethanol for 10 minutes and dry it.

[0012] 2. Seal one side of the dried zinc foil with Mara tape, drip ammonium persulfate solution on the unsealed side of the zinc foil, and rinse off the ammonium persulfate solution with deionized water after 10 minutes of reaction; place the zinc foil in citric acid solution for reaction for 12 hours, and rinse the reaction solution with deionized water after the reaction is completed;

[0013] 3. After drying the zinc foil obtained in step 2, the Mylar tape is removed to obtain a zinc negative electrode material with a highly exposed (101) crystal surface formed by citric acid etching.

[0014] The present invention uses commercial zinc foil as a sacrificial template, first polishes its surface to remove the dense oxide film produced on the surface, and prepares for the subsequent etching reaction. The purpose of using Mara tape is to isolate one side of the surface to prevent it from reacting with the solution. The purpose of ammonium persulfate treatment is to obtain an activated zinc negative electrode to react with a citric acid solution, thereby achieving the purpose of etching and forming an in-situ SEI.

[0015] The molar concentration of ammonium persulfate used in step 2 is 0.5 mol / L.

[0016] The molar concentration of the citric acid solution used in step 2 is 1.0 mol / L.

[0017] The drying temperature used in step 1 and step 3 is 60 ο C.

[0018] The third purpose of the present invention is to use the zinc negative electrode material with a high exposed (101) crystal face formed by citric acid etching as the negative electrode of an aqueous zinc ion battery, and assemble a full battery in sequence using a CR2032 negative electrode shell, a negative electrode with a diameter of 14 mm, a glass fiber separator with a diameter of 16 mm, 2 mol / L zinc sulfate as an electrolyte, a prepared positive electrode with a diameter of 12 mm, a gasket, a spring, and a CR2032 positive electrode shell.

[0019] Compared with traditional negative electrode materials, the present invention has the following main advantages and beneficial effects:

[0020] 1. The synthesis method adopted by the present invention is carried out at room temperature, and the characteristics of citric acid that has large binding energy with zinc (100) and (002) crystal planes and can react and etch away the (100) and (002) crystal planes are utilized, and the operation process is safe and simple.

[0021] 2. The new negative electrode synthesized by the present invention has the characteristic of highly exposed (101) crystal planes, wherein the highly exposed (101) crystal planes can greatly improve the stability and kinetic performance of the negative electrode, zinc ions can achieve rapid migration and uniform deposition on the surface of the negative electrode, and has a good inhibitory effect on hydrogen evolution and corrosion behavior.

[0022] 3. The highly exposed (101) crystal face prepared by the present invention forms a ZnS SEI protective layer after battery cycling, preventing direct contact between the exposed crystal face and the electrolyte, thereby inhibiting side reactions such as water decomposition. In addition, the excellent wettability of the ZnS SEI protective layer reduces the interfacial free energy, promotes the transfer kinetics of zinc ions, and contributes to uniform nucleation and deposition of zinc ions.

[0023] 4. The new negative electrode prepared by the present invention can achieve performance far exceeding that of traditional commercial zinc negative electrodes in stability tests, and exhibits excellent reversibility, and can stabilize the output of the battery in a full battery for practical application.

[0024] Therefore, the novel negative electrode synthesized by the method of the present invention has excellent electrochemical performance, high stability and good reversibility, and provides a method for protecting the negative electrode by etching in an aqueous zinc ion battery.

Brief Description of the Drawings

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0026] Figure 1This is a scanning electron microscope image of the negative electrode material with a highly exposed (101) crystal plane prepared in Example 1.

[0027] Figure 2 This is a scanning electron microscope image of a conventional commercial zinc foil of Comparative Example 1.

[0028] Figure 3 This is a scanning electron microscope image of the zinc foil treated with malic acid in Comparative Example 2.

[0029] Figure 4 This is a scanning electron microscope image of the zinc foil treated with oxalic acid in Comparative Example 3.

[0030] Figure 5 This is a scanning electron microscope image of the zinc foil treated with acetic acid in Comparative Example 4.

[0031] Figure 6 The XRD patterns of Example 1 and Comparative Example 1 are shown in FIG.

[0032] Figure 7 This is the XPS characterization diagram of sulfur 2p orbital in Example 1.

[0033] Figure 8 The results of Example 1 and Comparative Example 1 at 0.5 mA cm -2 and 0.5 mAh cm -2 Comparison chart of constant current charge and discharge cycles under conditions.

[0034] Fig. 9 The full battery assembled with the negative electrode prepared in Example 1 and Comparative Example 1 was subjected to 1A g -1 Cyclic comparison diagram under current density of . [Specific implementation method]

[0035] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0036] [Example 1]

[0037] This embodiment 1 describes a method for preparing a zinc negative electrode material with a highly exposed (101) crystal face formed by citric acid etching, and the steps are as follows:

[0038] (1) Preparation of zinc anode with highly exposed (101) crystal surface formed by citric acid etching

[0039] 1. First, use 800-grit sandpaper to polish the surface of the commercial zinc foil to remove the dense passivated zinc oxide on the surface. Then, use ethanol, deionized water, and ethanol to ultrasonically polish the zinc foil for 10 minutes and 60 minutes respectively. ο C drying;

[0040] 2. Seal one side of the dried zinc foil with Mara tape, drop 0.5 mol / L ammonium persulfate solution on the unsealed side of the zinc foil, and rinse off the ammonium persulfate solution with deionized water after 10 minutes of reaction; place the zinc foil in 1.0 mol / L citric acid solution for reaction for 12 hours, and rinse the reaction solution with deionized water after the reaction is completed;

[0041] 3. Zinc foil 60 obtained in step 2 ο After C is dried and the Mylar tape is removed, a zinc negative electrode material with a highly exposed (101) crystal surface formed by citric acid etching can be obtained.

[0042] The obtained zinc anode is used for the assembly of symmetric cells and full cells as follows:

[0043] Assembly of symmetrical battery: CR2032 negative electrode shell, negative electrode with a diameter of 14 mm, glass fiber separator with a diameter of 16 mm, 2 mol / L zinc sulfate as electrolyte, negative electrode with a diameter of 14 mm, gasket, spring, and CR2032 positive electrode shell are assembled into a symmetrical battery in sequence.

[0044] Assembly of the full battery: CR2032 negative electrode shell, a negative electrode with a diameter of 14 mm, a glass fiber separator with a diameter of 16 mm, 2 mol / L zinc sulfate as an electrolyte, a prepared positive electrode with a diameter of 12 mm, a gasket, a spring, and a CR2032 positive electrode shell are assembled into a full battery in sequence.

[0045] Figure 1 This is a scanning electron microscope (SEM) image of the zinc negative electrode material with a highly exposed (101) crystal plane formed by citric acid etching prepared in Example 1. It can be seen from the figure that after citric acid etching, a layered sheet structure will be produced on the surface of the zinc sheet, which has exactly the same morphological structure as the (101) crystal plane of the hexagonal closest packed Zn crystal, which proves from the morphology that the Zn (101) crystal plane is successfully exposed.

[0046] [Comparative Example 1]

[0047] The conventional commercial zinc foil was ultrasonically treated with ethanol, deionized water and ethanol for 10 minutes respectively, and then dried and cut into original sheets with a diameter of 14 mm for use as zinc negative electrodes. The assembly method of the symmetrical battery and the full battery is the same as that of Example 1, except that different zinc negative electrodes are used.

[0048] Figure 2This is a SEM image of a conventional commercial zinc foil in comparative example 1. As can be seen from the image, the surface of the zinc foil has a large number of unevenly distributed morphologies due to manufacturing, storage and transportation, which is also one of the reasons for the poor stability of the commercial zinc foil. The uneven morphology itself will accelerate the generation of dendrites.

[0049] [Comparative Example 2]

[0050] The experimental steps of this comparative example are basically the same as those of Example 1, except that the citric acid in step 2 is replaced by malic acid solution.

[0051] Figure 3 This is the morphology of the zinc foil formed by malic acid etching in comparative example 2. As can be seen from the figure, the surface of the zinc foil not only exposes the (101) crystal plane, but also exposes a large number of undesirable (100) crystal plane morphologies, which theoretically cannot inhibit the growth of dendrites.

[0052] [Comparative Example 3]

[0053] The experimental steps of this comparative example are basically the same as those of Example 1, except that the citric acid in step 2 is replaced by oxalic acid solution.

[0054] Figure 4 This is the morphology of the zinc foil formed by oxalic acid etching in Example 3. As can be seen from the figure, many blocky substances are generated on the surface of the zinc foil. Such a morphology is not conducive to solving the problem of increased local electric field caused by the "tip effect" and will inevitably lead to the growth of dendrites.

[0055] [Comparative Example 4]

[0056] The experimental steps of this comparative example are basically the same as those of Example 1, except that the citric acid in step 2 is replaced by acetic acid solution.

[0057] Figure 5 This is the morphology of the zinc foil formed by etching with acetic acid in comparative example 4. As can be seen from the figure, many large pore structures are formed on the surface of the zinc foil. Such a structure is similar to the arrangement of the (100) crystal plane, which will also cause epitaxial growth of the protrusions, causing the risk of dendrites piercing the diaphragm.

[0058] Figure 6 3 and 4. It can be seen from the XRD spectra of the negative electrodes prepared in Example 1 and Comparative Example 1 that after the etching reaction, no other crystalline materials are produced on the surface of the zinc foil. Moreover, from the comparison of the peak intensities, it can be seen that after citric acid etching, (100) and (002) are partially etched away, leaving a large amount of (101) crystal plane exposed.

[0059] Figure 7This is the XPS characterization of sulfur 2p orbital in the negative electrode of Example 1 after 10 cycles. It can be seen from the figure that after the battery cycle of Example 1, the surface S 2- The existence of ZnS SEI protective layer proves the formation of ZnS SEI protective layer. 2- The signal disappears, proving that the thickness of the SEI film of ZnS is small.

[0060] Figure 8 The results of Example 1 and Comparative Example 1 at 0.5 mA cm -2 and 0.5 mAh cm -2 Comparison of constant current charge and discharge cycles under the conditions of . It can be seen from the figure that the symmetrical battery assembled in Example 1 can stably cycle for more than 3980 hours under this condition, while the short circuit caused by dendrites occurred in the cycle of comparative example 1 after only 300 hours. In addition, due to the high proportion of (101) crystal planes, the kinetic process of zinc ion deposition can be promoted and the stability can be improved, which is specifically manifested in the constant current charge and discharge cycle, with a lower nucleation overpotential and a longer stable cycle.

[0061] Fig. 9 The full battery assembled with the negative electrode prepared in Example 1 and Comparative Example 1 was subjected to 1A g -1 Cycle comparison diagram under current density of . It can be seen from the figure that comparative example 1 has a capacity of 162.0mAh / g at the beginning of the cycle, and after 500 cycles, the remaining capacity is 100.7mAh / g, and the capacity decay is about 0.076% per cycle. In the process of cycling, Example 1 decays from the initial 190.8mAh / g to 181.0mAh / g, and the capacity decay is about 0.0026% per cycle, which is relatively small. Moreover, the coulombic efficiency of the full battery assembled in comparative example 1 begins to fluctuate at the beginning, and the stability of the battery is greatly reduced, while the full battery assembled in Example 1 always maintains a coulombic efficiency close to 100%.

[0062] In summary, the zinc negative electrode material with a highly exposed (101) crystal face formed by citric acid etching can achieve the purpose of protecting the negative electrode. At the same time, the present invention also provides a negative electrode protection method for aqueous zinc ion batteries using small molecule organic acids and etching strategies.

[0063] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A zinc negative electrode with a highly exposed (101) crystal face formed by citric acid etching, characterized in that: The Zn(101) crystal plane is largely exposed on its surface; The preparation method of the zinc negative electrode is as follows: (1) The surface of commercial zinc foil was polished to remove the surface zinc oxide, and then ultrasonicated for 10 min with ethanol, deionized water, and ethanol, respectively, and dried; (2) sealing one side of the dried zinc foil with a Mylar tape, dripping an ammonium persulfate solution on the unsealed side of the zinc foil, and washing away the ammonium persulfate solution with deionized water after reacting for 10 minutes; placing the zinc foil in a citric acid solution to react for 12 hours, and washing with deionized water to obtain a zinc foil; (3) Dry the zinc foil obtained in step (2) and remove the Mylar tape to obtain a zinc negative electrode.

2. A method for preparing a zinc negative electrode with a high exposed (101) crystal face formed by citric acid etching according to claim 1, characterized in that: The concentrations of the ammonium persulfate solution and the citric acid solution used in step (2) are 0.5 mol / L and 1.0 mol / L respectively.

3. The use of a zinc negative electrode with a high exposed (101) crystal face formed by citric acid etching in an aqueous zinc ion battery according to claim 1, characterized in that: Assemble the negative electrode shell, 14mm negative electrode, 16mm glass fiber separator, 2mol / L zinc sulfate electrolyte, 12mm diameter positive electrode, gasket, shrapnel, and positive electrode shell in order to form a full battery.

4. The use of a zinc negative electrode with a high exposed (101) crystal face formed by citric acid etching in an aqueous zinc ion battery according to claim 3, characterized in that: After the battery cycle, the zinc negative electrode will produce a ZnS solid electrolyte membrane protective layer on the negative electrode surface, making the negative electrode hydrophilic, which is beneficial to improving the negative electrode deposition / stripping performance.

Citation Information

Cited By

  • Preparation method of zinc composite electrode and application of zinc composite electrode in aqueous zinc ion battery

    CN121748259A